A retrospective evaluation of self-reported concussion history among male players drafted into professional Australian Rules Football - Reyes, J.; Shawdon, A.; Veale, J.; Willmott, C.; Makdissi, M. (Journal of Science and Medicine in Sport, 2024)
Introduction: Players are recruited yearly by Australian Football League (AFL) Clubs through the annual and mid-season drafts. As part of the draft process, players undergo a comprehensive medical evaluation which includes semi-structured interviews regarding concussion history and associated recovery. The purpose of the evaluation is to provide clubs with player medical and injury history prior to participation at the elite level, and to ensure optimal medical management of these future players. The study aimed to describe self-reported concussion history among male Talent Pathway Australian Football players. Methods: The retrospective cross-sectional study was approved by Monash University Ethics (HRECS 41112). All male players selected for the National or State Draft Combines from 2017 - 2023 were included. Standardised pre-draft medical screening questionnaire and semi-structured interviews were conducted by an experienced football doctor including a brief description of concussion to optimize reporting accuracy. De-identified data of self-reported concussion history were extracted from an internal database (SmartaBase) and analyzed using descriptive statistics on SPSS v.27 (IBM Ltd). Results: Of n = 1017 male players (M = 18.4, SD = 1.2 years), n = 435 (43%) reported having a previous concussion. Whilst most (n = 414, 95%) reported having sustained a prior concussion while playing Australian football, approximately one quarter (n = 100, 24.2%) presented to hospital with concussion. Players reported sustaining an average of two prior concussions (M = 1.94, SD = 1.28) while playing football (Median = 1, IQR = 1 to 3, range 1 to 7), with 25% (n = 108) reporting three or more previous concussions. Approximately one third (n = 146, 35.3%) of players experienced loss of consciousness (LOC). Of available responses (n = 405), 96% (n = 389) of players with prior concussion playing football reported that symptoms resolved within less than 14 days. Discussion: In this retrospective review of male Australian Football players entering the Draft Combine, 43% reported having experienced at least one previous concussion in football. Only 25% reported having three or more concussions. It remains important that players reporting multiple concussions on medical screening are further evaluated in detail to understand the nature of the injuries and potential future risks to the player. Only 4% of players reporting concussion experienced symptoms that persisted beyond 14 days, which is comparatively lower than that reported in similar adolescent cohorts from other studies (20% - 30%). This may be in part due to reporting bias, where data is derived largely from concussion clinics. Conversely, players in the current study may be under-reporting as they embark on their career in professional football. Reported LOC in only 35% of cases of previous concussion highlights the importance of broadening the definition of concussion outlined to players during medical screening, consistent with the most recently published Concussion In Sport Group definition. Impact/Application to the field: Rates of self-reported concussion history in this large cohort sample can help identify outlier responses during pre-season medical screening in Australian football and provide opportunities to improve player knowledge regarding concussion signs, symptoms and recommended care. Declaration: Investigators are employed by the Australian Football League.